Pengaruh Word Of Mouth (WOM) dan Customer Experience Terhadap Keputusan Pembelian Produk UMKM Yoghurt di Bandung Timur Pada Masa Pandemi Covid 19 - Elan Rusnendar; Giana Salma (Masoem University, 2022)
This study aims to find out how big the description and influence of Word Of Mouth and Customer Experience on the Purchase Decision of MSME Yogurt products in East Bandung during the Covid-19 pandemic. This study uses quantitative methods with descriptive and verification research approaches, with classical assumption testing, coefficients linear regression, correlation coefficient, hypothesis determination coefficient, t test and f test. The sample selection in this study was carried out based on non-probability sampling, using a purposive sampling technique with 100 respondents. The results of the data processing that the author did on the coefficient of determination test resulted in a contribution of 0.757 / 75.7% to purchasing decisions and the remaining 24.3% (100%-75.7%) are influenced by other variables. The results of the multiple correlation coefficient between Word Of Mouth and Customer Experience to Purchase Decisions is 0.870 or 87.0%. This shows that Word Of Mouth and Customer Experience have a relationship with Purchase Decisions, the results of research from respondents' overall responses regarding the effect of Word Of Mouth on purchasing decisions stated that respondents felt the need to tell others and Customer Experience on purchasing decisions stated that the more The better the Customer Experience, the higher the purchase decision will be.